‘Real-life’ experience with direct-acting antiviral agents for HCV after kidney transplant - Fabrizi, Fabrizio (2021)
Introductions and Objectives: The introduction of direct-acting antiviral (DAA) agents promises to change dramatically the management of hepatitis C in kidney transplant recipients, a patient group where the treatment of hepatitis C is historically challenging. The purpose of the current study was to assess (in a ?real-life? setting) the safety and efficacy of all-oral, interferon-free, direct-acting antiviral agents in kidney transplant recipients with HCV. Material and Methods: We performed a single-arm, multi-center study in a cohort (n = 95) of kidney transplant recipients who underwent antiviral therapy with DAAs. The primary end-point was sustained virologic response (SVR) (serum HCV RNA < 15 IU/mL, 12 weeks after treatment ended; SVR12). We recorded data on on-treatment adverse events (AEs), serious AEs, and laboratory abnormalities. Results: Various regimens were adopted at the discretion of the treating physician: elbasvir/grazoprevir (n = 11), paritaprevir/ritonavir/ombitasvir/dasabuvir (PrOD) regimens ± ribavirin (n = 23), and sofosbuvir-based regimens ± ribavirin (n = 61). The SVR12 rate was 93.7% (89/95) (95% CI, 88%; 98%), according to intention-to-treat analysis; three patients without viral response (n = 3) were found. Ribavirin was administered in 8 (8.4%) allograft recipients. The frequency of drop-outs was 4.2% (4/95) (95% CI, 0.2%; 8.2%); these were related to arthralgia/myalgia (n = 2), fatigue (n = 1), and lowered estimated glomerular filtration rate (eGFR) (n = 1). There were no differences with regard to serum creatinine and eGFR before and after antiviral therapy and during follow-up in the whole cohort. The patient who interrupted antiviral treatment due to raised serum creatinine was on sofosbuvir/daclatasvir regimen; one of the four drop-outs obtained SVR. Conclusions: All-oral, interferon-free therapy with DAAs for chronic HCV after kidney transplantation was effective and well-tolerated in a ?real?life? clinical setting. Identical results have been observed in patients with intact kidneys or advanced chronic kidney disease. Careful evaluation of kidney function over follow-up in kidney transplant recipients who received DAAs regimens is recommended. Clinical trials aimed to assess whether sustained viral response translates into improved patient/graft survival are under way.